Observation of black-capped capuchins (Cebus apella) feeding on an owl monkey (Aotus brumbacki) in the Colombian llanos - Carretero-Pinzón, Xyomara; Defler, Thomas R.; Ferrari, Stephen F. (Neotropical Primates, 2008)
No abstract